2022
DOI: 10.1128/msystems.00710-22
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Fecal Metabolomic Analyses across an Industrialization Gradient Reveal Shared Metabolites and Impact of Industrialization on Fecal Microbiome-Metabolome Interactions

Abstract: As the world becomes increasingly industrialized, understanding the biological consequences of these lifestyle shifts and what it means for past, present, and future human health is critical. Indeed, industrialization is associated with rises in allergic and autoimmune health conditions and reduced microbial diversity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 105 publications
1
1
0
Order By: Relevance
“…Ultra‐deep sequencing of Hadza hunter‐gatherers from Tanzania has identified many new microbial species and allowed for an in‐depth analysis of taxa associated with industrialised populations, and taxa that are under‐represented or lost relative to traditional societies (Carter et al., 2023 ). Analysis of the functional capacity encoded in the sequenced genomes also revealed differences (Table 1 ), which is broadly in agreement with a recent faecal metabolome study across several societies that demonstrated differences across an industrialisation gradient for some metabolites (for example amino acid‐conjugated bile acids, Haffner et al., 2022 ).…”
Section: The Gut Microbiota Fibre and Health In Different Populationssupporting
confidence: 86%
“…Ultra‐deep sequencing of Hadza hunter‐gatherers from Tanzania has identified many new microbial species and allowed for an in‐depth analysis of taxa associated with industrialised populations, and taxa that are under‐represented or lost relative to traditional societies (Carter et al., 2023 ). Analysis of the functional capacity encoded in the sequenced genomes also revealed differences (Table 1 ), which is broadly in agreement with a recent faecal metabolome study across several societies that demonstrated differences across an industrialisation gradient for some metabolites (for example amino acid‐conjugated bile acids, Haffner et al., 2022 ).…”
Section: The Gut Microbiota Fibre and Health In Different Populationssupporting
confidence: 86%
“…Regarding human stool samples, which reflect the gut metabolome, most of the published research has focused on characterizing its complex bacterial composition using next-generation microbial DNA sequencing and sophisticated metagenomic techniques. However, a growing number of microbiome researchers are recognizing that considerable information could be gained by using a more integrative approach that also includes comprehensive fecal metabolite analysis ( Karu et al, 2018 ; Haffner et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%